Anthocyanins from Aristotelia Chilensis Prevent Olanzapine-Induced Hepatic-Lipid Accumulation but Not Insulin Resistance in Skeletal Muscle Cells - Acuna-Castillo, C; Milla-Brito, L; Cubillos-Riffo, F; Del Campo-Sfeir, A; Rojo-Castillo, L; Calfio-Painemal, C (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Type 2 diabetes and obesity are major problems worldwide and dietary polyphenols have shown efficacy to ameliorate signs of these diseases. Anthocyanins from berries display potent antioxidants and protect against weight gain and insulin resistance in different models of diet-induced metabolic syndrome. Olanzapine is known to induce an accelerated form of metabolic syndrome. Due to the aforementioned, we evaluated whether delphinidin-3,5-O-diglucoside (DG) and delphinidin-3-O-sambubioside-5-O-glucoside (DS), two potent antidiabetic anthocyanins isolated from Aristotelia chilensis fruit, could prevent olanzapine-induced steatosis and insulin resistance in liver and skeletal muscle cells, respectively. HepG2 liver cells and L6 skeletal muscle cells were co-incubated with DG 50 µg/mL or DS 50 µg/mL plus olanzapine 50 µg/mL. Lipid accumulation was determined in HepG2 cells while the expression of p-Akt as a key regulator of the insulin-activated signaling pathways, mitochondrial function, and glucose uptake was assessed in L6 cells. DS and DG prevented olanzapine-induced lipid accumulation in liver cells. However, insulin signaling impairment induced by olanzapine in L6 cells was not rescued by DS and DG. Thus, anthocyanins modulate lipid metabolism, which is a relevant factor in hepatic tissue, but do not significantly influence skeletal muscle, where a potent antioxidant effect of olanzapine was found. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.